PENGEMBANGAN PROFESIONALISME PROFESI PENDIDIK DI INDONESIA - Ali Ridho; Suklani Suklani (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Professionalism for teachers and lecturers is a capability that must be owned by both in carrying out their duties. The teacher's ability to be able to develop the potential of his students in learning is a task that he must do. Professional teachers and lecturers must have several abilities to carry out their duties as educators. Law No. 14 of 2005 concerning Teachers and Lecturers, in which it is explained that teachers are able to understand, master, and are proficient in utilizing new learning resources and have pedagogical, personal, professional, and social competencies as part of teacher professionalism as educators. This research was conducted to discuss the professionalism criteria of a teacher and lecturer as educators. This research uses a qualitative approach, through literature studies on articles, books, and writings related to the discussion. The results of the study show that professional teachers and lecturers are educators who are able to: (1) deliver their students to the standards set by the government, with various basic abilities that must be achieved, (2) Teachers are required to have qualified competence, for an educator who working in formal schools, starting from elementary to high school levels, (3) Lecturers have an important task, namely teaching a science at a deep level. Higher education as an institution that organizes education, has an important role in national development. Higher education has the main task of educating the nation's next generation to master science and technology, as well as being a locomotive for national development.